Il laser scanning e CloudCUBE per le grotte di Naica - Canevese, Erminio Paolo; Tedeschi, Roberta; Mora, Paolo (GEOmedia, 2008)
Laser scanning and CloudCube for Naica caves On May 2007, Virtualgeo, a geomatic software development and communication company, took part in the first official expedition to Mexico. The Project, coined "Naica", involves researchers from ten universities, four companies and several laboratories. Virtualgeo carried out the survey by applying laser scanning technology to hypogeal caves covered with selenite crystals. The data was processed using CloudCUBE, a proprietary software designed to manage and model 3D point clouds. The first results of the laser scanning survey of a spectacular "forest of crystals” are presented here.